Deep Learning Model in Science Learning: Bibliometric Analysis - Happy, Nurina; Tomi Apra Santosa; Siti Fatimah Hiola; Ifa Safira; Nur Latifah; Dewanto; Muh. Safar; Aat Ruchiat Nungraha (Science Education and Application Journal, 2025)
The deep learning model is one of the learning models that can be applied in science learning. Research related to deep learning has grown very rapidly in recent years. Research on deep learning models has produced many theoretical and empirical findings. Many trends have emerged to highlight the complexity and dynamics of deep learning models in science learning.  This study aims to discover the latest trends in deep learning model research in science learning. This study uses a bibliometric approach of analysis based on the Google Scholar database. Based on this study's title, abstract, and keywords, it produced 872 studies from 2015-2024. The results of this study show that the deep learning model in this learning has increased significantly in 2022. The increase in research on deep learning models shows the importance of applying deep learning models in learning.